Stereoselective Synthesis of the C19–C39 Fragment of Bastimolide A - Kumar, Nemilikonda Sravan; Ramulu, B. Janaki; Ghosh, Subhash (SynOpen, 2021)
This paper describes the synthesis of the C19–C39 fragment of the antimalarial natural product bastimolide A via addition of a functionalized C19–C26 alkyne fragment to a C27–C39 aldehyde fragment. Opening of a terminal epoxide and Noyori asymmetric reduction were used as key steps in the synthesis.
Keywords: bastimolide A; antimalarial activity; stereoselective synthesis; epoxide opening; Noyori asymmetric reduction